Genetic prediction of the casual relationship between micronutrients and ER+ breast cancer: a Mendelian randomized study - Fu, Wei-Da; Wang, Jin-Qiu; Luo, Jin; Wei, Ming-Ze; Dai, Yong-Ping; Wang, He-He (Frontiers in Genetics, 2025)
BackgroundEstrogen receptor-positive (ER+) breast cancer, a prevalent subtype of breast malignancy, demonstrates complex etiological associations with multiple risk factors. Micronutrients, as essential nutritional components for human physiology, may potentially influence the pathogenesis and progression of breast carcinoma. This investigation employs Mendelian randomization (MR) methodology to assess causal relationships between 15 micronutrients and ER+ breast cancer.MethodsIn this study, instrumental variables (IVs) for 15 micronutrients were extracted from the genome-wide association studies (GWAS) database, including copper, calcium, carotene, folate, iron, magnesium, potassium, selenium, vitamin A, vitamin B12, vitamin B6, vitamin C, vitamin D, vitamin E, and zinc. Concurrently, summary data related to ER+ breast cancer were obtained from the FinnGen database. Following the selection of appropriate IVs, we conducted a two-sample MR analysis. This analytical framework incorporated comprehensive sensitivity analyses to evaluate potential heterogeneity and horizontal pleiotropy, with the inverse variance weighted (IVW) method established as the principal analytical approach.ResultsThe findings of our study revealed a significant causal relationship between vitamin B6 and ER+ breast cancer. Notably, genetically predicted elevated vitamin B6 levels were significantly associated with an increased risk of ER+ breast cancer [Odds Ratio (OR): 1.275; 95%Confidence Interval (CI): (1.017–1.600); P = 0.035]. In contrast, no statistically significant associations were observed between the other 14 micronutrients and ER+ breast cancer risk (P > 0.05 for all).ConclusionOur results indicated that higher concentrations of vitamin B6 may be positively associated with ER+ breast cancer risk, and further research is needed to elucidate the underlying biological mechanisms of this association. This study provides new insights into understanding the role of micronutrients in breast cancer.